The Relationship between Religion and State in the Context of Globalization: A Theoretical and Practical Analysis in the Modern Era - Mohammad Rifky; Mutohharun Jinan (Analisis: Jurnal Studi Keislaman, 2025)
The relationship between religion and the state is a classic issue in social and political science studies that remains relevant amidst the dynamics of globalization and increasing religious pluralism. Globalization not only influences economic and political structures but also demands that states restructure the relationship between religion and the state to ensure religious freedom, protect minority rights, and maintain social stability and cohesion. Countries with strong religious traditions, such as Saudi Arabia, the Vatican, and Israel, tend to position religion as the primary source of legitimacy in state policy, either through theocratic patterns or religious-secular configurations. Meanwhile, multicultural countries such as Indonesia and India implement a symbiotic pattern by seeking a balance between the role of religion and the principle of pluralism. This study uses a library method with a qualitative descriptive-analytical and critical approach. Data were obtained from primary and secondary literature analyzed through a process of classification, reduction, and thematic analysis. The results show that countries with strong religious legitimacy tend to face serious challenges in managing pluralism and protecting the rights of religious minorities. Conversely, multicultural countries that adopt a symbiotic pattern are relatively more adaptive, although they still face the potential for social conflict. This finding confirms that the success of relations between religion and state is highly dependent on policies that are inclusive, democratic, and oriented towards respecting human rights.